First insights into the identification of bone and antler tools used in the indirect percussion and pressure techniques during the early postglacial. (22nd November 2016) - David, É.; Sørensen, M.
Abstract: With the interest for the technological options that were taken by the prehistoric groups to subsist, there is a field of research left empty in terms of archaeological records dated to the 8th and 7th millennia cal BC. It concerns the tool kit made from bone and antler used in Europe by stone knappers to work the lithic raw material by pressure and indirect percussion. Based on morpho-technological aspects, this paper presents a first list of recognized archaeological osseous artefacts employed in indirect and pressure lithic reduction. These are punches, pectoral and shoulder sticks, as well as bone elements involved in the lever systems. This investigation is made in the frame of a larger research project aiming at discussing both origin and agent responsible for the introduction of the "inset technology"—conical core pressure blade concept together with the slotted bone tools—appearing in the southern Scandinavia at ca. 7300 cal BC. Results are promising and experiments enabling characterization of the bone and antler tools used in the debitage by pressure and indirect percussion will be soon undertaken.